The Effectiveness of Using Flashcards on Teaching English Vocabulary - Wulandari, Ellok Mustika (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study focuses on English vocabulary teaching and learning. Vocabulary as all words in a language, the richness of words possessed by a speaker or writer, words used in a field of science, a list of words arranged like a dictionary, and practical and brief explanations. The study uses a pre-experimental research design, one group pretest-posttest. The result1 shows the students' Mean pretest score was 55,3333, and the posttest score was 78,3333. It shows that the posttest score (after giving Flashcards treatment) was higher than the pretest score (before treatment). The researcher obtains that t-value -6,965 was more elevated than t-table 2,131 in the significant level 0,05.